El uso de datos de personas fallecidas y el derecho a la memoria póstuma - Stacey Freire, Andrea Cristina (2025)
This article focuses on the study of the use of personal data of deceased individuals and their relationship with the right to the posthumous memory, a concept that advocates for respect and dignity in preserving the legacy of the deceased people. In the digital era, where personal information persists beyond a person’s life, the lack of clear regulations on the management of this data poses serious ethical and legal challenges. Through a thorough analysis of current legislation and doctrine, this work examines topics of great relevance such as the data of deceased individuals, privacy, ethics, to establish that the improper use of this data affects both the deceased person and their families. The general objective is analyzing whether the improper use of the data of deceased people violates the right to the posthumous memory. This research was conducted through the qualitative modality with the use of research methods and techniques that allowed the compilation of information through which it was determined that it is necessary to develop a robust and coherent legal framework that protects the data of living individuals but also extends beyond death, ensuring that the memory of the deceased is preserved with respect and dignity that they deserve, thereby, strengthening the protection of post mortem data.